Influence of Service Quality and Food Experience on Tourists Satisfaction a Study on Houseboat Tourism in Kerala: Exploring the Impact of Service Quality and Food Experience on Tourist Satisfaction in Houseboat Tourism (Journal of Advances and Scholarly Researches in Allied Education, 2019)
In human beings, curiosity and the spirit of adventure are innate. The desire to travel will always develop in order to see new sights and new experiences and to live in different environments. During their stay in these destinations, tourism is a temporary short-term movement of people to destinations other than the areas in which they currently live and work and their activities. This implies that the demand for travel and tourism goods will rise and it will be possible to market travel and tourism. In modern economies, the service sector plays an increasingly significant role. One of the biggest service sectors in the world is travel and tourism. It also plays a very important role in the economy and has stimulated other economies' growth. Moreover, among the service industries, the tourism industry is one of the growing foreign pioneers. In other industries, such as retail, transport and building, this creates a strong flow-through impact. The role of tourism, through income and foreign exchange, the preservation of cultures and historical heritage, the promotion of national growth and the essential and critical factor in job opportunities, highlights the importance of tourism. Tourism is an important economic activity and continues to be the fastest growing industry and is thus usually included in the top ten industries in the country (retail and wholesale trade, agriculture, real estate, banking and insurance, industry, transport, engineering and machinery, chemicals, tourism, textiles).